Amplifying Education: A Case Study in Advancing Academic Centres at Norwich University - Morris, Travis; Tara, Tara Kulkarni; Ku, Yangmo Ku; Liptak, Megan (Scientia militaria : South African journal of military studies, 2024)
Norwich University, the oldest private military college in the United States, aims to prepare future military and civilian leaders to navigate leadership and educational challenges successfully. One method of preparing leaders is through academic centres. Drawing on seven years of data from the John and Mary Frances Patton Peace and War Center and six years at the Center for Global Resilience and Security at Norwich University, this article shows how this task is accomplished by formally establishing research centres that exist outside of regular academic programming. The centres are uniquely positioned to understand the priorities of the US Reserve Officer Training Corps Cadet Command and the US Department of Defense to prepare future junior military leaders to be prepared for twenty-first-century security challenges. Particular attention is given to how experiential learning, leadership laboratories, and research have prepared cadets to be effective junior military leaders. For each core area, we apply Bloom's hierarchical models to maximise cognitive, affective, and sensory learning objectives. Examples are provided to elucidate the paradigm and outlined objectives further. The article concludes by highlighting the impact of centres across the Norwich community. Relevant International Symposium of Military Academies (ISOMA) 2023 sub-themes: y Academic programmes and the development of military knowledge and skills y The reality and challenges of the quality of education in military academies: experiences and lessons learned